Enhanced K +-channel-mediated endothelium-dependent local and conducted dilation of small mesenteric arteries from ApoE -/- mice - Beleznai, T; Takano, H; Hamill, C; Yarova, P; Douglas, G; Channon, K; Dora, K (2011)
AimsAgonists that evoke smooth muscle cell hyperpolarization have the potential to stimulate both local and conducted dilation. We investigated whether the endothelium-dependent vasodilators acetylcholine (ACh) and SLIGRL stimulated conducted dilation and whether this was altered by deficiency in apolipoprotein E (ApoE -/-).Methods and resultsIsolated mesenteric arteries were cannulated, pressurized, and precontracted with phenylephrine. Agonists were either added to the bath to study local dilation or were restricted to one end of arteries to study conducted dilation. An enhanced sensitivity to both ACh and SLIGRL was observed in mesenteric arteries from ApoE -/- mice compared with wild-type controls. Inhibition of nitric oxide (NO) synthase blocked ACh responses, but had no effect on maximum dilation to SLIGRL. SLIGRL increased endothelial cell Ca 2, hyperpolarized smooth muscle cells, and fully dilated arteries. The NO-independent dilation to SLIGRL was blocked with high [KCl] or Ca 2-activated K +-channel blockers. The hyperpolarization and dilation to SLIGRL passed through the artery to at least 2.5 mm upstream. The conducted dilation was not affected by a deficit in ApoE and could also be stimulated by ACh, suggesting NO itself could stimulate conducted dilation.ConclusionIn small mesenteric arteries of ApoE -/- mice, NO-independent dilation is enhanced. Since both NO-dependent and-independent pathways can stimulate local and conducted dilation, the potential for reducing vascular resistance is improved in these vessels. © 2011 The Author.